2017
DOI: 10.1016/j.juro.2016.09.114
|View full text |Cite
|
Sign up to set email alerts
|

Failed Primary Bladder Exstrophy Closure with Osteotomy: Multivariable Analysis of a 25-Year Experience

Abstract: Proper immobilization with modified Buck traction and external fixation, immobilization time greater than 4 weeks and undergoing osteotomy performed by a pediatric orthopedic surgeon are crucial factors for successful primary closure with osteotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…5 The obstruction at the urethra or bladder neck presents an immediate danger to the upper urinary tract, leads to urinary tract infections, and is difficult to definitively treat. 16 One girl developed this complication, and upper urinary tract dilation was documented. This child is undergoing clean intermittent catheterization and close follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The obstruction at the urethra or bladder neck presents an immediate danger to the upper urinary tract, leads to urinary tract infections, and is difficult to definitively treat. 16 One girl developed this complication, and upper urinary tract dilation was documented. This child is undergoing clean intermittent catheterization and close follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of this complication is unclear, but aggressive tailoring at the bladder neck, whether during a CPRE or staged approach or a compartment syndrome effect causing vascular compromise in the deep pelvis after complete reapproximation of the pubic symphysis after osteotomies, are potential factors . The obstruction at the urethra or bladder neck presents an immediate danger to the upper urinary tract, leads to urinary tract infections, and is difficult to definitively treat . One girl developed this complication, and upper urinary tract dilation was documented.…”
Section: Discussionmentioning
confidence: 99%
“…However, osteotomy was required as pelvic bone malleability markedly decreased afterward [ 18 ]. Previous studies concluded that closure of the bladder without pelvic osteotomy showed a higher incidence of premature hip arthrosis, but when combined bladder closure and pelvic osteotomy, it increased the odds of a successful outcome [ 10 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 This is of particular importance during surgical reconstruction in those undergoing delayed primary closure or repeat closure for prior failed closure. [4][5][6][7] Postoperative immobilization of the pelvis and lower extremities is essential after pelvic osteotomy in instances when no internal fixation is utilized. Various postoperative immobilization methods have been described, including Bryant traction, spica cast immobilization, and external fixation with Buck's traction.…”
mentioning
confidence: 99%
“…Pelvic osteotomies aim to reduce tension during surgical reconstruction, thereby decreasing the risk of dehiscence and vesicocutaneous fistula 3 . This is of particular importance during surgical reconstruction in those undergoing delayed primary closure or repeat closure for prior failed closure 4–7 …”
mentioning
confidence: 99%